THE CONCEPT OF MAN IN AHMAD ASRORI’S ANTHROPOLOGY OF TASAWUF (JOURNAL OF INDONESIAN ISLAM, 2017)
this paper aims at introducing a new approach in the study of man called the anthropology of tasawuf. It combines two ways of thinking. The one looks at man rationally while the other spiritually. In the proposed approach, man is defined as both knowing and spiritual being. This kind of approach is a form of critic against the currents of thought which look at man only positively, and other intuitively. The former is duly represented by most –although not all- Western scholars, while the latter by most Sufis. The new approach is also a kind of reminder that tasawuf cannot always be looked at simply and exclusively in terms of its practices and ritualism. It is above all, a discourse and system of knowledge. By bringing forward the thought of Surabaya-based sufi master named Ahmad Asrori, the paper tries to show 1) what the anthropology of tasawuf is all about, and 2) what tasawuf actually has to say concerning man and his essence. The new approach also relates the notion of man and his essence with the idea of how he acquires knowledge. Hence, it speaks not only of man ontologically but also epistemologically. In another sense, the paper is also an effort to introduce to the outsiders that tasawuf in Indonesia -which is particularly associated with Ibn Arabian tradition- is dynamic and growing.